Curating in the Open: A Case for Iteratively and Openly Publishing Curatorial Research on the Web. (October 2016) - Owens, Trevor
Abstract: Through a case study of using social media tools to open up part of the curatorial research process for an online exhibit on the history of astronomy at the Library of Congress, I offer some initial ideas about how an open approach to sharing curatorial research could significantly expand the impact and reach of such work. Drawing on three distinct emerging conceptions and frameworks for the idea of "open" (open notebook science, linked open data, and open innovation) I suggest how this case study can be used to guide work with existing simple and inexpensive tools and how it could also inform the development of future tools, services and exhibit development methods. This work builds on an ongoing discussion of open data in libraries, archives, and museums. To date, most of that dialog is about object records and not about the stories and narratives cultural heritage institutions tell about them. I suggest ways to make the production of cultural heritage data, as well as the final outputs, part of an open and transparent process.